Cause analysis and research progress of phlebitis caused by venous indwelling needle (静脉留置针致静脉炎的相关因素及防治研究进展) - CHEN Yin (陈颖); TIAN Jing (田婧); CHU Yina (初伊娜); HU Yaxin (胡雅鑫); GAO Xinxia (高新霞) (中西医结合护理)
Venous indwelling needle has the advantages of protecting blood vessels and reducing repeated puncture. It is widely used in clinical settings, but there are still problems such as phlebitis and infection in the treatment process, which affects the use efficiency of indwelling needle. This paper mainly summarizes the influencing factors and nursing measures of phlebitis caused by venous indwelling needle, so as to improve nurses' ability to identify and control the influencing factors of various phlebitis, reduce the incidence of complications, reduce the incidence of phlebitis caused by indwelling needle, and improve the use efficiency of indwelling needle. (静脉炎是使用留置针常见的并发症之一。本文主要对静脉留置针致静脉炎的影响因素及护理措施进行综述, 以提高护士对各类静脉炎影响因素的识别与控制能力, 减少并发症发生, 降低留置针致静脉炎发生率, 提高留置针使用效能。)